The Impact of Psychological Capital and Social Capital on Residents’ Mental Health and Happiness During COVID-19: Evidence From China - Zhao, Xincheng; Liu, Qian; Zhang, Shan; Li, Tinghua; Hu, Bin (Frontiers in Psychology, 2022)
Objective: This paper mainly studies the mediating and interactive effects of social capital on psychological capital and the feeling of happiness under the impact of COVID-19. The COVID-19 pandemic, which began in 2020, has taken a toll on people's mental health and dented their hopes for the future. People's life style and economic conditions have changed, which has impacted people's confidence in life. This increases the likelihood that people will develop mental anxiety or depression. Therefore, it is of great significance to study the influence of psychological capital and social capital on people's subjective psychology and happiness experience. It is important to examine the impact of psychological and social capital on people's subjective psychology and experience of well-being. Methods: Using Ordered Probit model, this paper studies the independent influence and interaction between psychological capital and social capital on people's happiness. The reason for choosing Ordered Probit model is that residents' subjective well-being is an Ordered variable. Structural equation model is suitable for analyzing the mediating effect of variables, so this paper uses structural equation model (SEM) to study the mediating effect of social capital on psychological capital and residents' happiness. Results: The regression results show that both psychological capital and social capital are significantly positively correlated with residents' happiness when a series of control variables are considered. Psychological capital and social capital have significant positive interaction, and psychological capital promotes the effect of social capital on happiness. The influence coefficient of psychological capital on residents' happiness is greater than that of social capital. It shows that happiness is more influenced by residents' subjective psychological experience. The interaction coefficient of psychological capital and social capital is significant (1% level), indicating that the two have mutually reinforcing effects on happiness. Health, income class, real estate, stranger trust, age and urban household registration all have significant positive effects on happiness. However, money view, female, education level and happiness have a negative relationship. The structural equation model is used to estimate the mediating effect and the total effect. The mediating effect of psychological capital on happiness is partly transmitted through social